Plasmodium berghei serine/threonine protein phosphatase PP5 plays a critical role in male gamete fertility. Issue 9 (August 2019) - Zhu, Xiaotong; Sun, Lin; He, Yang; Wei, Huanping; Hong, Mingyang; Liu, Fei; Liu, Qingyang; Cao, Yaming; Cui, Liwang
Graphical abstract: Highlights: Recombinant Plasmodium berghei PP5 (rPbPP5) had phosphatase activity and was sensitive to PP1/PP2A inhibitors. PbPP5 was localised in the parasite cytoplasm and under the plasma membrane in some stages. A Pbpp5 gene knockout severely reduced male gamete formation and fertility. PP1/PP2A inhibitors reduced microgametocyte exflagellation and ookinete conversion. Abstract: Sexual development in malaria parasites involves multiple signal transduction pathways mediated by reversible protein phosphorylation. Here, we functionally characterised a protein phosphatase, Ser/Thr protein phosphatase 5 (PbPP5), during sexual development of the rodent malaria parasite Plasmodium berghei . The recombinant protein phosphatase domain displayed obvious protein phosphatase activity and was sensitive to PP1/PP2A inhibitors including cantharidic acid (IC50  = 122.2 nM), cantharidin (IC50  = 74.3 nM), endothall (IC50  = 365.5 nM) and okadaic acid (IC50  = 1.3 nM). PbPP5 was expressed in both blood stages and ookinetes with more prominent expression during sexual development. PbPP5 was localised in the cytoplasm of the parasite and highly concentrated beneath the parasite plasma membrane in free merozoites and ookinetes. Targeted deletion of the pbpp5 gene had no influence on asexual blood-stage parasite multiplication or the survival curve of the infected hosts. However, male gamete formation and fertility were severely affected, resulting in almost complete blockade of ookinete conversion and oocyst development in the Δpbpp5 lines. This sexual development defect was rescued by crossing Δpbpp5 with the female defective Δpbs47 parasite line, but not with the male defective Δpbs48/45 line, thus confirming the essential function of the pbpp5 gene in male gamete fertility. Furthermore, the aforementioned PP1/PP2A inhibitors all had inhibitory effects on exflagellation of male gametocytes and ookinete conversion. In particular, endothall, a selective inhibitor of PP2A, completely blocked exflagellation and ookinete conversion at ∼548.3 nM. This study elucidated an essential function of PbPP5 during male gamete development and fertility.